Augmented reality adoption intention among travel and tour operators in Malaysia: mediation effect of value alignment - Alam, Syed Shah; Masukujjaman, Mohammad; Susmit, Samiha; Susmit, Sumaiya; Abd. Aziz, Hassanuddeen (Emerald Publishing Limited, 2022)
Purpose – This study evaluated the determinants of augmented reality (AR) adoption in Malaysia’s travel and tour operator sectors through an integrated technology organization-environmental (TOE) and diffusion of innovation (DOI) model. Design/methodology/approach – The TOE and DOI were considered the primary theoretical models but are combined and extended by including few additional variables. Data were collected from 220 respondents of travel and tour operating businesses in Malaysia and analyzed by applying PLS structural equation model technique. Findings – The empirical results established that perceived cost, relative advantages, complexity and compatibility, observability, competitor pressure, value alignment, customer pressure, and trialability are positively connected with the behavioral intention except for external support. The results reveal that value alignment partially mediates the association between relative advantages and behavioral intention, complexity and behavioral intention, compatibility and behavioral intention, perceived cost and behavioral intention except in between trialability and observability. Originality/value – This research is unique as the value alignment construct is included in the model, and thus it fulfills the literature gap by adding the mediation construct. This study contributes to enhancing AR’s understanding of the Malaysian travel and tour operator industry through the lenses of owners or managers. It offers an integrated model that combines the TOE and DOI models, rare in this sector, and can be replicated or extended with validated scales.